Análisis del recurso humano que labora en Establecimientos Hoteleros en el Cantón Quevedo 2022 - Santana Carriel, Josue Cristopher (2022)
The present study seeks to analyze the human resource that works in the hotel establishments in the Quevedo canton, where its main objective is to find out if the staff is trained for its established area, which will allow identifying the main signs that can prevent the growth of establishments. hoteliers, the methodologies used were interview and survey to obtain the relevant data, to generate and analyze the data and apply the inductive method and be able to provide a general conclusion, 3 hotels in the city were taken into account, the interview was carried out realizing that there is a trained personnel, however, the quality of human talent personnel could be improved.